2013
DOI: 10.1016/j.applthermaleng.2012.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Size effects of a portable two-phase electronics cooling loop

Abstract: Using a state of the art one dimensional, two-phase, dynamic system model, the size effects of a portable two-phase microchannel electronic cooling system are investigated using different refrigerants (R134a, R236fa, R245fa). Special attention is given to the accumulator size and its limitations for portable applications. An analytical model is developed to investigate the accumulator size effect on the loop and compared to the numerical results obtained from the system model. The influence of various loop par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The need for solutions able to deal with such high heat fluxes has motivated the investigation of a huge variety of methods and technologies for heat transfer enhancement [2]. Solutions based on liquid [3] and two-phase [4,5] flows have been proved to be effective in dissipating large heat fluxes.…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…The need for solutions able to deal with such high heat fluxes has motivated the investigation of a huge variety of methods and technologies for heat transfer enhancement [2]. Solutions based on liquid [3] and two-phase [4,5] flows have been proved to be effective in dissipating large heat fluxes.…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…Thanks to the works of Bejan [45][46][47] on entropy generation minimisation (EGM), awareness of the importance and potential of the second law in the analysis of the performance of heat exchangers grew, giving rise to several works and different techniques, a review of which can be found in [48]. More recently, researchers have dealt with the optimisation of micro heat exchangers [49][50][51] in terms of the first and second law, with new and interesting results obtained when conjugate effects are considered. An extensive body of work on the combined use of PEC and EGM has been produced by Zimparov, who extended the former method [52,53] and co-authored [54,55] with some recent contributions where the relative performance of different cross-sections under laminar flow conditions and either H or T boundary conditions are studied: see [56] for further references.…”
Section: Introductionmentioning
confidence: 99%
“…The performance and reliability of electronic components and assemblies strongly depend on their thermal state and characteristics [1][2][3]. In electronics, natural convection is the preferred heat transfer mode, given its numerous advantages.…”
Section: Introductionmentioning
confidence: 99%